The influence of adaptive games on the psycho-emotional state of military personnel during rehabilitation - Kateryna Mulyk; Alexander Skaliy; Tetyana Grynova; Tatiana Skaliy; Kseniia Polovinko (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: to evaluate the impact of classes using adaptive games on the psychological rehabilitation of military personnel in a health care facility.